Skeletonema species in a temperate estuary: a morphological, molecular and physiological approach. Issue 3 (2nd July 2016) - Hevia-Orube, Joana; Orive, Emma; David, Helena; Laza-Martinez, Aitor; Seoane, Sergio
Abstract : The genus Skeletonema is frequently found in the Bilbao estuary (Northern Spain) where it is broadly distributed along the salinity gradient. By means of morphological and molecular analyses, six strains belonging to three species, Skeletonema costatum, Skeletonema dohrnii and Skeletonema menzelii, have been identified. To know if they can grow actively in the different water masses or whether they are simply displaced by the tide, their response to salinity (5, 10, 15, 20, 25, 30 and 35 psu) was measured with a Pulse Amplitude Modulation fluorometer, providing the specific growth rates, the maximal quantum efficiency of Photosystem II ( F v / F m ) and the relative electron transport rate. All three species can be considered euryhaline, growing in a good physiological state between 5 and 35 psu. The maximum growth rates were 1.17 d −1 for S. costatum (strain Bc18EHU) at 15 psu; 1.61 d −1 for S. dohrnii (strain Bc21EHU) at 25 psu and 1.7 d −1 for S. menzelii (strain Bc30EHU) at 20 psu. The rapid light curves revealed that the three species are acclimated to the high light intensities which occur in the estuary from March to September.